Identification success rates in the post-Spanish Civil War mass graves located in the cemetery of Paterna, Spain: Meta-research on 15 mass graves with 933 subjects - Sanchis-Gimeno, Juan A.; Iglesias-Bexiga, Javier; Schwab, Marisol E.; López-García, Gema; Ariza, Eloy; Calpe, Alejando; Mezquida, Miguel; Nalla, Shahed; Ercan, Ilker (Forensic science international, 2024)
Spain suffered a Civil War between 1936 and 1939 that ended with the victory of the National Forces led by General Franco. Once the Spanish Civil War ended, 2238 subjects were executed and buried in several mass graves in the Cemetery of Paterna, one of Spain's largest mass grave sites. Efforts to locate and identify all the victims of the mass graves of the Paterna cemetery are ongoing, but the actual data of the percentage of DNA identifications remains uncertain. Following this, we conducted a meta-research study including 15 mass graves and 933 subjects to determine the DNA identification rates in the mass graves of the Paterna cemetery. We found that the total proportion of identified subjects in the mass graves was 15.9 % (95 % CI: 10.0–22.9). Moreover, we found that the model between the identification success rate (ISR) and the number of relatives that donated DNA (NRTDD) in the mass graves of the cemetery of Paterna was ISR = NRTDD−0.424. Results obtained about the proportion of identified subjects and the model between the ISR and the NRTDD imply the need for a scientific reflection between all the research groups involved in the identification tasks to modify deficiencies and update identification protocols to obtain better future results. •More than 2200 subjects lay in mass graves in the Cemetery of Paterna.•Fifteen mass graves with 933 subjects were analyzed.•The proportion of identified subjects was 15.9 % (95 % CI: 10.0–22.9).•The model between the ISR and the NRTDD was: ISR = NRTDD-0.424.